2015
DOI: 10.1093/cid/civ455
|View full text |Cite
|
Sign up to set email alerts
|

Less Bone Loss With Maraviroc- Versus Tenofovir-Containing Antiretroviral Therapy in the AIDS Clinical Trials Group A5303 Study

Abstract: NCT01400412.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…Net differences in percentage change in BMD between groups were significant at 24 weeks at both the spine and hip (spine: −0.91%; p=0.001 and hip: −0.61%; p=0.001)[44**]. Further, in HIV, studies comparing TDF-containing ART and ART without TDF in ART-naïve HIV-infected individuals have consistently shown that ART without TDF leads to less BMD decline over the first 48 to 96 weeks of treatment[45*, 46] as well as less increase in bone turnover markers[47*, 48]. Last, in virologically suppressed, HIV-infected participants, switching from a TDF-containing regimen to an alternative NRTI or an NRTI-sparing regimen also leads to improvement in bone turnover markers, including sclerostin, a selective regulator of bone formation through the Wnt pathway[49*] and results in increase in BMD[50*].…”
Section: Introductionmentioning
confidence: 99%
“…Net differences in percentage change in BMD between groups were significant at 24 weeks at both the spine and hip (spine: −0.91%; p=0.001 and hip: −0.61%; p=0.001)[44**]. Further, in HIV, studies comparing TDF-containing ART and ART without TDF in ART-naïve HIV-infected individuals have consistently shown that ART without TDF leads to less BMD decline over the first 48 to 96 weeks of treatment[45*, 46] as well as less increase in bone turnover markers[47*, 48]. Last, in virologically suppressed, HIV-infected participants, switching from a TDF-containing regimen to an alternative NRTI or an NRTI-sparing regimen also leads to improvement in bone turnover markers, including sclerostin, a selective regulator of bone formation through the Wnt pathway[49*] and results in increase in BMD[50*].…”
Section: Introductionmentioning
confidence: 99%
“…The overall 60% lower bone resorption in the ZOL arm relative to the placebo arm and the corresponding 11% relative higher BMD at the lumbar spine observed with ZOL at 48 weeks are the largest reported effect sizes for any prophylactic intervention directed at ameliorating ART-induced bone loss. At 48 weeks, supplementation with vitamin D and calcium carbonate in treatment-naive, HIV-infected patients in a recent study resulted in a relative treatment difference in total hip BMD of 1.86% [23], while in the A5303 study, the use of a TDF-sparing ART regimen was associated with relative treatment differences in total hip and lumbar spine BMD of 0.89% and 1.47%, respectively [9].…”
Section: Discussionmentioning
confidence: 96%
“…A5303 was a phase 2, prospective, double‐blind, placebo controlled, multicenter, 48‐week study of maraviroc 150 mg or tenofovir disoproxil fumarate (tenofovir) 300 mg, each plus darunavir/ritonavir 800/100 mg and emtricitabine 200 mg in participants infected with the R5‐tropic HIV‐1 (Taiwo et al., 2015). Participants were ART naïve adults (aged ≥18 years) recruited from 33 AIDS Clinical Trials Group (ACTG) and four Adolescent Trials Network study sites in the USA.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were ART naïve adults (aged ≥18 years) recruited from 33 AIDS Clinical Trials Group (ACTG) and four Adolescent Trials Network study sites in the USA. Participants in A5303 were randomized in a 1:1 ratio and stratified by plasma HIV‐1 RNA < or ≥100,000 copies/ml and age <30 or ≥30 years (Taiwo et al., 2015). …”
Section: Methodsmentioning
confidence: 99%